Effects of biological geotextiles on aboveground biomass production in selected agro-ecosystems - R. Bhattacharyya (2018)
© 2011 Elsevier B.V. Biological geotextiles have considerable potential for soil erosion control, but few studies have been completed on their effects on aboveground biomass production. Hence, field experiments were conducted to investigate the hypothesis that the use of geotextile mats would increase aboveground biomass. We investigated the crop and weed aboveground biomass at four international sites (in China, Thailand, Vietnam and Lithuania). These sites were selected due to the severity of soil erosion problems and feasibility of using biological geotextiles in highlands. In Lithuania, imported Borassus and Buriti mats and indigenous wheat straw mats were used on roadside slopes. In China, Thailand and Vietnam, both Borassus mats and other biological geotextiles were constructed using indigenous local materials (bamboo, rice straw, wheat straw and maize stalks). Results show that biomass production was ∼6 to 53% higher in plots with biological geotextiles compared with the plots with no geotextile treatment. In Lithuania, cover of Borassus and Buriti mats during 2006–2007 increased perennial grass productivity by ∼50 and 18%, respectively, compared with plots with no cover (5.29 Mg ha−1). In China, plots with contour planting covered by rice straw mats had ∼29% higher wheat yield than the plots with no geotextile treatment (1.98 Mg ha−1). Likewise, rice straw, Borassus and maize stalk mat-cover on the plots with no geotextile treatment had significant effects in increasing yields of faber bristle grass (by ∼52%) and maize by 18% and 14% in two separate experiments in China. In Thailand, results (May 2007–June 2008) showed that plots under contour planting mulched with bamboo mats had ∼40 and 26% higher (P < 0.05) sweet corn (Zea mays) and lablab bean (Lablab purpureous) yields, respectively, than plots under contour planting only. Plots under contour planting (without a geotextile cover) had 2.5 and 0.61 Mg ha−1of sweet corn and lablab bean grain yield production, respectively. In Vietnam, Borassus, maize stalk and bamboo mat cover on bare plots had ∼53, 47 and 35% higher soybean yields, respectively, than the plots with no geotextile treatment (6.6 Mg ha−1). Increased biomass in plots under biological geotextiles was due to soil and moisture conservation. Erosion rates significantly decreased by 15–20% in Lithuania and 67–98% in South-East Asia, compared with the plots with no geotextile cover. Thus, biological geotextiles significantly increased aboveground biomass production and generally contributed to decreased soil loss under diverse soil and climatic conditions.